The Evolving Roles Political Connections in Firm Performance: Insights from a Two-Decades Review - Widyastuti, Arie; Wiryono , Sudarso Kaderi; Nainggolan , Yunieta Anny (Jurnal Manajemen Teknologi, 2025)
Abstract. This study examined the impact of political connections on firms' performance. Using bibliometric data, we analysed key research areas, top journals, important studies, leading scholars, and prominent institutions and countries in this field of research. Our review of 709 articles demonstrates a significant increase in publications on this topic, highlighting the valuable role of political ties for firms across both emerging and developed economies. Greater attention is paid to not only business and economic areas, such as market and financial performance, corporate governance, and mergers and acquisitions, but also the economic consequences of green and sustainable practices on the performance of politically connected firms. Due to the interdisciplinary nature of research on political connections, this study provides valuable insights for decision-makers in using political connections as a non-market strategy by mapping knowledge development in the research field over the last two decades, as well as facilitating future research to more easily identify relevant references and presenting emerging themes in the research domain. Keywords: Firms' performance, political connections, bibliometric analysis, knowledge mapping, web of science